Self-assembly of metal–organic polyhedra into supramolecular polymers with intrinsic microporosity - Arnau Carné-Sánchez (Nature Portfolio, 2018)
Porosity in metal–organic materials typically relies on highly ordered crystalline networks, which hinders material processing and morphological control. Here, the authors use metal–organic polyhedra as porous monomers in supramolecular polymerization to produce colloidal spheres and gels with intrinsic microporosity.